Effects of Calsium Carbonat on Hardness and Wear Behaviour of Brass-Epoxy Brake Lining Pad. - Nugroho, Fajar (SENATIK STT Adisutjipto, 2019)
Brake lining pad is important in driving safety. It must be able to stop the vehicle as quickly as possible. Calcium carbonate is The purpose of this study was to identify the effect of calcium carbonate to the brake brass-epoxy lining pad. Calcium carbonate meet have good physical properties, such as having low porosity and fine particles while brass has a good heat conductor and is corrosion resistant so it is resistant to heat. The tests carried out on brake pads include wear and hardness tests. The results showed that the optimal wear rate in a dry state (40% calcium carbonate-20% brass-40% epoxy) was 0.0352 mm²/kg. While the wear rate in wet conditions (20% calcium carbonate-40% brass-40% epoxy) was 0.0396 mm²/kg. The hardness brake lining pad (20% calcium carbonate - 40% brass -40% epoxy) was  176.44 kg/mm².